Evaluation of instantaneous vibration parameters of a snowboard with a prototype granular dissipator - Bajkowski, J. M.; Dyniewicz, B.; Bajer, C. I.; Bajkowski, J. (Sports Engineering, 2022)
A container partially filled with loose plastic granules was attached to the shovel of the snowboard to suppress large-amplitude lateral vibrations by dissipating energy through non-conservative multi-granule interactions. A custom laboratory stand allowed to evaluate the performance using a full-scale snowboard deck. The response of the system with a prototype granular dissipator was measured for free lateral vibrations of the initially deflected board and under prescribed sinusoidal base motion. The damping characteristics for different fill ratios of the container were obtained using a direct method of nonparametric identification. The applied Hilbert-Huang transform-based vibration analysis method gave more insight into the board`s damping performance than the logarithmic decrement analysis. The results show that using the granular dissipator with a predestined number of granules increases the damping capacity at large amplitudes but is less effective at small amplitudes. At best, the damping factor was 70% higher when the granular dissipator was used than when the board was damped only intrinsically.